Effects of gamma-irradiation on nanostructured Na-bentonite silicate layers at room temperature - Ismayilova, M.K. (Вопросы атомной науки и техники, 2021)
The aim of this paper to study the effects of γ-rays on nanostructured Na-bentonite clay from Alpoid deposit. The effect of high doses (up to 256 kGy) of γ-radiation on the short-range structural organization in montmorillonite was studied using infrared spectroscopy. Significant change attributable to irradiation was observed at dose of 57 kGy. No significant changes were observed after 57 kGy of γ-radiation. A small variation in the water content was noted but it is not systematic. The results show that the montmorillonite structure can accumulate high doses of radiation with damage. The modifications most likely to be generated by the radiation were expected to be within the silicate layers. The morphology of the nanocomposites was studied with scanning electron microscopy. In this paper, the effects of ionizing radiation on the Na-bentonite clay investigated by FT-IR method. These spectra show the suitability of FT-IR study of mineral surfaces and the changes in the spectra brought about by the surface phenomena.